Early Mobilisation and Pain Intensity in Post–Caesarean Section Patients: Implications for Nursing Care - Imelda Rahmayunia Kartika; Fitria Nola Rezkiki; Niken Raysiska (PT Pubsains Nur Cendekia, 2026)
Background: Cesarean delivery, or Cesarean section, is one of the most common surgical procedures performed to ensure maternal and fetal safety during childbirth. However, the procedure often results in postoperative pain caused by tissue trauma, which may hinder the mother’s recovery process. Uncontrolled pain can limit physical movement, delay early mobilisation, and reduce the mother’s ability to perform self-care and infant care activities. Early mobilisation is widely recognised as an important non-pharmacological nursing intervention that may help reduce pain intensity and promote faster postoperative recovery. Therefore, understanding the relationship between early mobilisation and pain intensity is important to support evidence-based nursing care. Aims: to examine the relationship between early mobilisation and pain intensity among post–cesarean section patients at Regional Hospital, Bukittinggi. Methods: This study employed a quantitative approach with a cross-sectional design. The population consisted of all post–cesarean section patients hospitalised in the maternity ward during the study period. A total of 68 respondents were recruited using a total sampling technique. Data were collected using an early mobilisation observation checklist and a pain intensity measurement using the Numeric Rating Scale. Data analysis included univariate analyses to describe the distribution of variables and bivariate analyses using the Chi-square test to assess the relationship between early mobilisation and pain intensity. Results: The results showed that most respondents performed good early mobilisation (66.2%), and a considerable proportion experienced mild pain intensity (39.7%). Statistical analysis revealed a significant relationship between early mobilisation and pain intensity (p = 0.001). Conclusions: early mobilisation is significantly associated with lower pain intensity among post–cesarean section patients. These findings highlight the importance of encouraging early mobilisation as part of nursing care to support pain management and enhance postoperative recovery among mothers following cesarean delivery.